Evidence for endorsement of a trait-oriented approach to the examination of psychopathy - Berman, Katheryn M (My University, 2017)
Researchers have long assumed that psychopathic traits are associated with lower endorsement and adherence to moral values (Koch, 1891; Cleckley, 1941). This assumption is emphasized in fictional depictions of psychopathy (Furham, Daoud, & Swami, 2009), but modern empirical studies suggest a more complex state of affairs. In particular, the some studies suggest that psychopathy is generally associated with low levels of moral value endorsement (Jonason et al., 2014), whereas others find evidence of positive and negative associations, depending o the specific types of values assessed (Djeriouat & Trémolière, 2014). The present study seeks to provide clarification on how psychopathy relates to value endorsement by examining how the common four factors of psychopathy (Hare & Neuman, 2008) are individually related to value endorsement. Data were analyzed from 531 participants who completed the Moral Foundations Questionnaire, the Portrait Values Questionnaire, and the Self-Report Psychopathy Scale-III on Amazon’s Mechanical Turk website. Correlations and hierarchical regressions revealed a general trend toward alignment with lay theories of psychopathy, but notable exceptions emerged. Findings are examined with respect to the dimensionality of psychopathy, research methodology, and the importance of replication. Implications of the results and proposed directions for future research are also discussed.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science - Psychology Cognitive and Affective Science
Keywords: Values; Conduct of life; Psychopaths